Közigazgatás és hatalomgyakorlás Szálasi Ferenc kormánya idején - Kovács, Zoltán András (Acta Scientiarum Socialium, 2014)
Public Administration and Exercise of Power during the Szálasi Government in Hungary After the failed attempt by Regent Miklós Horthy to extricate Hungary from the Axis alliance, the concomitant Hungarist takeover on 15 October 1944 resulted in a far-right government that wanted to break with the customary ways of exercising power since 1920 and transform the public administration system of Hungary. The paper surveys the specific methods of exercising power, the conceptions for reorganizing public administration and how these ideas were put into practice during the Szálasi government.